Moses Norton (ca. Late 1720s-1773) - Glover, Richard (ARCTIC, 1982)
. As his father had, Norton did some exploring when his boss, Ferdinand Jacobs, sent him to Chesterfield Inlet in 1762. He returned to report reaching its very end and finding that no hoped-for Northwest Passage existed there. That autumn, Jacobs went to command York Fort, and Norton succeeded him at Churchill. He now had opportunities to display what the late Professor Rich generously called his "uncommon energy and perception". One may allow the "energy", for Norton was full of ideas, but they were too often impractical for his "perception" to be very impressive. One was a notion that live moose could usefully be sent to England, . and by their next boat the Company ordered Norton to send no more livestock home. . in 1765 he persuaded his employers to start a whaling business at Churchill. The result was disastrous. A century later bowheads were profitably hunted around Southampton Island, but Norton ordered his whalers to stay south of Marble Island. There only four whales were caught in seven years, and in 1772 the Company cancelled this enterprise after losing over 20,000 [Pounds Sterling]. Another of Norton's brainwaves concerned the copper which had long been known to exist in the North. . In 1765 Norton hired two Chipewyans, Idotliazee and Matonabbee, to find its source. Three years later . [Norton] persuaded his employers to send Samuel Hearne on his three famous journeys to the Coppermine in 1769-72. On the joureys we can say here only that Norton's crazy planning ensured the failure of the first two. . This third journey also caused a bitter quarrel between Norton and Hearne, for Norton tried to force Hearne to take along some of his Cree relatives. Hearne, who had enough of Norton's kin on his earlier journeys, refused; and thereafter, he writes, Norton "used every means in his power to treat me ill." It is therefore unfortunate that nobody but Hearne has left any description of Norton's personality; Hearne's picture of him living "in open defiance of every law, human and divine", is so lurid that ...